2018
DOI: 10.3390/biom8020042
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Binding Proteins with Disordered Structure and Their Role in Secretion, Storage, and Cellular Signaling

Abstract: Calcium is one of the most important second messengers and its intracellular signaling regulates many aspects of cell physiology. Calcium ions, like phosphate ions, are highly charged and thus are able to alter protein conformation upon binding; thereby they constitute key factors in signal transduction. One of the most common calcium-binding structural motifs is the EF-hand, a well-defined helix-loop-helix structural domain, present in many calcium-binding proteins (CBPs). Nonetheless, some CBPs contain non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…In contrast, in the absence of Ca 2+ ion, the RTX parallel β-roll motif repeat structure appeared to be disordered [27,28]. A previous study showed that the RTX parallel β-roll motif repeat structure became disordered and adequately unfolded in the absence of Ca 2+ ion [6][7][8][27][28][29]. In agreement with our previous laboratory work (CD spectra), in the absence of Ca 2+ ion (0 mM CaCl 2 ), the AMS8 lipase secondary structure, especially β-sheet content was decreased [14].…”
Section: Destabilization Of Rtx Parallel β-Roll Motif Repeat the Strumentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, in the absence of Ca 2+ ion, the RTX parallel β-roll motif repeat structure appeared to be disordered [27,28]. A previous study showed that the RTX parallel β-roll motif repeat structure became disordered and adequately unfolded in the absence of Ca 2+ ion [6][7][8][27][28][29]. In agreement with our previous laboratory work (CD spectra), in the absence of Ca 2+ ion (0 mM CaCl 2 ), the AMS8 lipase secondary structure, especially β-sheet content was decreased [14].…”
Section: Destabilization Of Rtx Parallel β-Roll Motif Repeat the Strumentioning
confidence: 94%
“…The RTX proteins show signs of an intrinsically disordered protein in the absence of Ca 2+ ion. Many experimental works have been conducted to prove the contribution of Ca 2+ ion [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. However, the study is scarce to further analyze the contribution of Ca 2+ ion toward the folding and stabilization of the RTX protein structure through in silico approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high sequence similarity with NopE proteins suggests that a common molecular “post secretion host-sensing” conformational switch may exist in both beneficial and pathogenic T3SS-dependently secreted proteins. Ca 2+ -dependent disorder-to-order transitions are typical of numerous proteins secreted by type 1 secretion systems 33,34 . It is thus remarkable that the MIIA domain of the coral pathogen resides in a T3SS gene cluster, but exhibits a similar Ca 2+ -dependent transition from a disordered secretion-adapted state to a more compact structure with hydrophobic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK-interacting and spindle-stabilizing protein-like (Gene ID: S24_1645) is involved in regulating milk synthesis [91,[104][105][106]. EF-hand domain-containing 2 (Gene ID: S25_42968291) is one of the most common calcium-binding structural motifs, and a well-defined helix-loop-helix structural domain, present in many calcium-binding proteins, has been identified in milk [107][108][109][110]. Our results support these important insights into the synthesis of milk proteins and potential targets for the future improvement of milk quality.…”
Section: Plos Onementioning
confidence: 99%